2013
DOI: 10.1093/hmg/ddt356
|View full text |Cite
|
Sign up to set email alerts
|

Methylomics of gene expression in human monocytes

Abstract: DNA methylation is one of several epigenetic mechanisms that contribute to the regulation of gene expression; however, the extent to which methylation of CpG dinucleotides correlates with gene expression at the genome-wide level is still largely unknown. Using purified primary monocytes from subjects in a large community-based cohort (n = 1264), we characterized methylation (>485 000 CpG sites) and mRNA expression (>48K transcripts) and carried out genome-wide association analyses of 8370 expression phenotypes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
149
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(157 citation statements)
references
References 39 publications
6
149
2
Order By: Relevance
“…However, we observed both positive and negative correlations between DNAm and gene expression in other site types, which is consistent with previous studies that have challenged the assumption that DNAm is inversely associated with gene expression. 42,52 The results of this study reflect the biological complexity of epigenetic data and underscore the need for multidisciplinary approaches to study how DNAm may contribute to the social patterning of disease. We found that childhood SES was associated with DNAm in approximately the same number of stress-and inflammationrelated genes (3 stress and 2 inflammation), whereas adult SES was primarily associated with DNAm in inflammation-related genes (5 inflammation-related genes vs. 1 stress-related gene).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…However, we observed both positive and negative correlations between DNAm and gene expression in other site types, which is consistent with previous studies that have challenged the assumption that DNAm is inversely associated with gene expression. 42,52 The results of this study reflect the biological complexity of epigenetic data and underscore the need for multidisciplinary approaches to study how DNAm may contribute to the social patterning of disease. We found that childhood SES was associated with DNAm in approximately the same number of stress-and inflammationrelated genes (3 stress and 2 inflammation), whereas adult SES was primarily associated with DNAm in inflammation-related genes (5 inflammation-related genes vs. 1 stress-related gene).…”
Section: Discussionmentioning
confidence: 64%
“…Criteria for elimination included: 'detected' expression levels in <10 % of MESA samples (detection P-value cut-off D 0.01), probes that contain a SNP, probes with low variance across samples (<10 th percentile), or overlap with a non-unique region. A detailed description of the quantitation and data processing procedures used for DNAm and gene expression can be found in Liu et al 42 Chip effects were adjusted prior to analysis.…”
Section: Gene Expressionmentioning
confidence: 99%
“…In addition to the genetic association analysis of DNA methylation levels (see section 3.1), the relationship between DNA methylation and Gene expression levels have been integrated at the genome-wide scale (Gibbs et al, 2010; Liu, Ding, et al, 2013). Although epigenetic markers can induce the transcriptional regulation, the epigenetic modification may not be sufficient to cause changes of gene expression levels.…”
Section: Overview Of Omics Technologies and Association Studiesmentioning
confidence: 99%
“…The integrative approach of multi-omic data may enhance the understanding of the molecular dynamics underlying the pathophysiology of diseases, and may lead to novel strategies for early detection, prevention and treatment of human diseases. Given the increasing number of population studies collecting multi-omic data but limited overview of the methodological framework for integrative analyses (Liu, Ding, et al, 2013; Petersen et al, 2014; Shah et al, 2015), we summarize the analytical methods for high-throughput multi-omic data, and provide an updated analytical framework to incorporate genomic, epigenomic, transcriptomic, proteomic, and metabolomics data for the emerging field of multi-omic association study of human diseases. In this article, we do not cover the topic of disease classification and prediction, which does not aim to understand the biological and functional roles of omic markers (Wan & Pal, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has been applied to HapMap cell lines [14] , whole blood from healthy human subjects [16] and human monocytes [17] . Furthermore, some studies have combined these types of data to better understand complex diseases such as breast cancer [18] or type 2 diabetes [19] .…”
mentioning
confidence: 99%